An axonemal alteration in apical endometria of human adenomyosis. Issue 6 (23rd April 2021) - Khan, Khaleque N; Fujishita, Akira; Suematsu, Takashi; Ogawa, Kanae; Koshiba, Akemi; Mori, Taisuke; Itoh, Kyoko; Teramukai, Satoshi; Matsuda, Katsuya; Nakashima, Masahiro; Kitawaki, Jo
Abstract: STUDY QUESTION: Is there any change in the distribution of microvilli and microtubules in the apical endometria of women with adenomyosis? SUMMARY ANSWER: We observed microvilli damage in the apical endometria and an axonemal alteration characterized by abnormal distribution of longitudinal bundles of microtubules within microvilli in women with adenomyosis. WHAT IS KNOWN ALREADY: Human adenomyosis has a negative impact on female fertility. Abnormal utero-tubal sperm transport, tissue inflammation and toxic effect of chemical mediators have been proposed as contributing factors. Inflammation-induced damage of mucosal cilia in the Fallopian tube has been reported. However, information on inflammation-induced damage of microvilli on the apical endometrial cells and its core bundles of microtubules in adenomyosis remains unknown. STUDY DESIGN, SIZE, DURATION: This is a prospective cohort study with subjects undergoing laparoscopic surgery or hysterectomy for clinical indication and evaluations of endometrial biopsy samples in two academic university hospitals. During the period between March 2015 and December 2018, endometrial biopsy samples were prospectively collected from 15 control women and 45 women with adenomyosis for immunohistochemical analysis and a separate cohort of 10 control women with cervical intraepithelial neoplasia Grade 3 (CIN3) and 20 women with adenomyosis for analysis by immunohistochemistry and transmission electron microscopy (TEM). PARTICIPANTS/MATERIALS, SETTING, METHODS: For immunohistochemical study, endometrial biopsy samples were prospectively collected from 15 control women with fibroids, 25 women with focal adenomyosis and 20 women with diffuse adenomyosis after surgery. The diagnosis of fibroid and adenomyosis was made clinically by transvaginal ultrasonography and magnetic resonance imaging and confirmed by histology. Immunohistochemical analysis was performed retrospectively using antibody against CD68 (marker of macrophages) in endometrial biopsy specimens of women with and without adenomyosis. TEM was performed with the apical endometria collected from a separate cohort of 10 control women with CIN3 and 20 women with focal and diffuse adenomyosis for the identification of any change in the distribution of microvilli and longitudinal bundles of microtubules within microvilli. MAIN RESULTS AND ROLE OF CHANCE: Comparing to control endometria and contralateral side, tissue infiltration of macrophages (Mφ) in the endometria was significantly higher on the ipsilateral side of focal adenomyosis ( P  = 0.02 and P  = 0.03, respectively) and anterior/posterior walls of diffuse adenomyosis ( P  = 0.01 for both). In a subgroup analysis of patients with focal adenomyosis with and without symptoms, the endometria of symptomatic women displayed a tendency of higher Mφ infiltration on the ipsilateral side than in asymptomatic women ( P  = 0.07). Comparing to contralateral side endometria of symptomatic women, Mφ infiltration was significantly higher in the endometria of symptomatic women collected from the ipsilateral side of focal adenomyosis ( P  = 0.03). We found a significantly less tissue infiltration of Mφ in the endometria of women with CIN3 than that in endometria of women with focal adenomyosis. TEM analysis showed that number of microvilli in the endometria was significantly decreased on the ipsilateral side ( P  = 0.003) comparing to that on the contralateral side of focal adenomyosis. The Chi-squared test indicated that cases with abnormal (disruption in the normal arrangement of 9 peripheral pairs + 1 central pair) microtubules (MT) were significantly higher in women with adenomyosis than in cases with normal patterns ( P  = 0.0016). While contralateral side displayed significantly less abnormal MT ( P  = 0.0002), ipsilateral side of focal adenomyosis showed significantly higher abnormal MT ( P  = 0.0164) comparing to normal patterns. Cases with symptomatic adenomyosis showed significantly higher abnormal MT than normal MT ( P  = 0.0004). An axonemal alteration characterized by abnormal structural distribution of microtubules within microvilli in the apical endometria in response to endometrial inflammation may be involved in adverse reproductive outcome in women with adenomyosis. LIMITATIONS, REASONS FOR CAUTION: The average age of women in this study was high that may be associated with overall decline in fertility regardless of the presence or absence of adenomyosis or endometriosis. We collected endometrial biopsy samples from two completely separate cohorts of women for analysis by immunohiostochemistry and TEM. We need future follow-up study with increased sample size and from the same patients to precisely clarify the mechanistic link between axonemal alteration and negative fertility outcome. WIDER IMPLICATIONS OF THE FINDINGS: Our current findings may have some biological implication to better understand the endometrial epithelial biology and pathology in women with adenomyosis and may open the avenue for future study in other reproductive diseases. The ultra-structural abnormalities of microvilli and microtubules in the apical endometria in response to tissue inflammatory reaction may clarify the possible association between negative fertility outcome and adenomyosis. Our findings may be clinically useful during counseling with symptomatic patients with adenomyosis desiring pregnancy. STUDY FUNDING/COMPETING INTEREST (S): This work was supported by Grants-in-Aid for Scientific Research from the Ministry of Education, Sports, Culture, Science and Technology of Japan. There is no conflict of interest related to this study. TRIAL REGISTRATION NUMBER: N/A.